As (des)sonorizações e a neutralização da vibrante: atitudes e concepções lingüísticas - Schneider, Maria Nilse (Contingentia, 2008)
This article discusses linguistic attitudes and conceptions (beliefs and prejudices) of 20 teachers regarding the ‘German accent’ ((de)voicing of consonants and neutralization of the vibrant) and their implications in their social practices in school lessons, in three German-Portuguese bilingual communities in Rio Grande do Sul. To conclude with, a reflection about how teachers’ conceptions relate to the treatment they dispense to linguistic traces in face to face interactions. The present investigation is inserted in the Interactional Sociolinguistics and in the Sociolinguistics field, specifically in linguistic variation and bilingual studies, and it is especially rooted in linguistic attitudes and conceptions. This research matches instruments and analytical categories of both quantitative and qualitative approaches, examining both teachers’ practices and their linguistic attitudes and conceptions. The results point to educational and identity conflicts which are reflected in speakers’ attitudes of solidarity or linguistic differentiation regarding the use and rating of linguistic variation, as well as in the treatment dispensed to the linguistic features of these communities. Keywords: linguistic variation and identity; linguistic attitudes; bilingualism; social interaction.